Design and experimental demonstration of a mechatronic solution for endovascular catheters - Brett,PN; Du,X; Assadi,MZ; Rodriguez,y Baena F; Liu,F; Hinchliffe,R; Thompson,M (2018)
This paper describes a mechatronics approach that provides vascular surgeons with the perception of movement and tissue interaction in the vicinity of the tip of a catheter in endovascular procedures. The current system described is experimental and used in phantom units. It integrates 3D visualization generated from scan with real-time tactile sensing in the vicinity of the tip of the catheter to update on the nature of tissue interaction, the curvature and relative orientation of the catheter sleeve and guide wire. This approach offers superior perception by the clinician, in contrast with current application of catheters used in this application. By being well informed of conditions at the working environment of the catheter tip the clinician will be able to administer therapies with greater precision in the surgical task and within a reduced operating time. The approach will reduce risk for patients and significantly reduce risks for the clinician, who is currently exposed to high doses of ionizing radiation during the process of catheter guidance.